Students' Learning Perception in Engineering, Health and Education during Emergency Remote Education in Chile - Villarroel, Verónica; Gonzalez Sanzana, Alvaro (My University, 2023)
Higher education institutions around the world had to implement an emergency remote education (ERE) modality due to the COVID-19 pandemic. This study aimed to determine the individual and relational factors that affect the perception of learning in engineering, education, and health students during emergency distance education. Through a quantitative, non-experimental, and correlational study, an online survey was administered to a sample of 929 higher education students regarding their ERE experience. They were surveyed regarding their perceived learning, empathy, classroom interaction, self-regulation of learning, positive agency, student engagement, learning approaches, and use of digital resources. Data was analyzed using quantitative methods, namely correlations, comparisons of means and a linear regression analysis. Education students showed a more positive perception of learning, used a deep learning approach, and rated more positively the empathy shown by their professors and the possibilities for class participation than other students. Engineering students had the lowest scores on perceived learning and on almost all other variables. In general, students with a better perception of learning presented a higher engagement in their studies and a lower use of surface learning approach.
Keywords: covid-19; higher education; internet; pandemic; remote education